2020
DOI: 10.1002/ijfe.2416
|View full text |Cite
|
Sign up to set email alerts
|

The impact of exchange rate and exchange rate volatility on Mauritius foreign direct investment: A sector‐wise analysis

Abstract: This article analyses the structure of FDI inflow in different sectors of the Mauritian economy. While undertaking this investigation, we primarily allow interaction of FDI with exchange rate and exchange rate volatility and with other equally important macroeconomic variables such as trade openness, human capital, GDP, wages and salaries, gross capital formation, and inclusion of a dummy variable to assess the Mauritian Corporate Income Tax (CIT) reform of 2007. Sectors classified as manufacturing, financial,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…They suggested that a currency depreciation of the host currency significantly increased FDI inflow. These results remained consistent with different modeling strategies such as a panel vector autoregressive model in Kodongo and Ojah (2013) or even with an autoregressive distributed lag model in Muhammad et al (2018) and Moraghen et al (2020). It is noteworthy that Blonigen (1997), Dewenter (1995), Stevens (1998), Y. Xing (2006) and X. Xing and Wan (2006) contradicted these arguments.…”
Section: Literature and Theoretical Frameworksupporting
confidence: 80%
See 1 more Smart Citation
“…They suggested that a currency depreciation of the host currency significantly increased FDI inflow. These results remained consistent with different modeling strategies such as a panel vector autoregressive model in Kodongo and Ojah (2013) or even with an autoregressive distributed lag model in Muhammad et al (2018) and Moraghen et al (2020). It is noteworthy that Blonigen (1997), Dewenter (1995), Stevens (1998), Y. Xing (2006) and X. Xing and Wan (2006) contradicted these arguments.…”
Section: Literature and Theoretical Frameworksupporting
confidence: 80%
“…The complexity of the problem is such that it cannot be reduced to a unidimensional one. The inclusion of other classical determinants (as is explicitly demonstrated in Fauzel et al, 2017; Moraghen et al, 2020) is thus necessary to unpack the variance of the dependent variable. Doing so immediately allows for an increasingly precise determination of the consequences of direct and indirect effects between the explanatory variables.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Kyereboah‐Coleman and Agyire‐Tettey (2008) reported that in Ghana RER volatility impacts FDI inflow negatively while FDI is increased due to political factors. Moraghen et al (2020), analysed the impact of exchange rate and exchange rate volatility FDI in on Mauritius, they reported that the exchange rate and exchange rate volatility have negligible impact on FDI inflow in the short run, a real depreciation has been beneficial over the long term in enhancing FDI inflow. Pozo (2001), in a study on the USA, found that FDI increases if exchange rate uncertainty decreases in the short run when using a conditional measure of exchange rate volatility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings of this study reveal that gross domestic product, openness, and exchange rate, have a positive relationship with foreign direct investment but, world crude oil prices and volatility of exchange rate have negative relationship with foreign direct investment. Moraghen et al (2020) used semi-annual data from 1990 to 2015 to examine the structure of FDI inflow in different sectors of the Mauritian economy. The cointegration bound test indicated a long-run systematic link between the variables, justifying the usage of an ARDL model.…”
Section: Empirical Reviewmentioning
confidence: 99%